Perceived Organizational Support and Job Satisfaction Among Nursing Instructors in Nursing Educational Institutes, People’s Republic of Bangladesh - Baral, Rina Rani; Sirakamon, Somjai; Chontawan, Ratanawadee (Nursing Journal CMU, 2020)
Job satisfaction is crucial for the retention of nursing instructors. Studies indicated that perceived organizational support influences job satisfaction. This descriptive correlational study aimed to describe perceived organizational support and job satisfaction, and to examine the relationship between perceived organizational support and job satisfaction among nursing instructors. The sample consisted of 186 nursing instructors working in 43 nursing educational institutes in the People’s Republic of Bangladesh. The research instruments used were the Demographic Data Form, the Survey of Perceived Organizational Support (SPOS), and the abridged Job Descriptive Index (aJDI). The reliabilities of the SPOS; and the aJDI were 0.90 and 0.82, respectively. Data were analyzed using descriptive statistics and Spearman’s rank-order correlation coefficient. The results of this study indicated as follows: Perceived organizational support among nursing instructors was at a moderate level. Job satisfaction among nursing instructors was at a moderate level. There was a statistically significant moderate positive relationship between perceived organizational support and job satisfaction. The findings of this study could be used by the administrators of nursing educational institutes in developing strategies to improve perceived organizational support; thereby, job satisfaction of nursing instructors would be increased.